The architectural and cultural reception of the Temple of Apollo at Bassai and its frieze from 1811 to 2009 - O'Neill, Suzanne (Trinity College (Dublin, Ireland). Department of Classics, 2010)
This thesis is an analysis of the architectural and cultural reception of the Temple of Apollo at Bassai and its frieze from 1811 to 2009. The reception of this globally important UNESCO listed monument is an area of research that has been largely overlooked by academics. The aim of this multi-disciplinary thesis has been to fill this obvious academic void.
Keywords: Classics, Ph.D.; Ph.D. Trinity College Dublin